Grouper fry propagation method - XU MEIYING; WANG HAILING; XU JIAJING (2014)
The invention discloses a grouper fry propagation method, which belongs to the technical field of marine culture. The grouper fry propagation method comprises the following steps: (1) selecting parent fish; (2) breeding the parent fish; (3) collecting fertilized ova; (4) manually regulating and controlling the incubation of the fertilized ova; (5) manually regulating and controlling the breed of fry, advanced fry and juvenile fish. The method is rational in design and has strong operability; by adding Vc, VE and compound traditional Chinese medicine immunopotentiator in a feed fed in a parent fish culture process, the potential disease in the bodies of the parent fish can be prevented, the immunologic functions of the bodies of the parent fish are enhanced, and mature gonad development of the parent fish is promoted, so that the fish naturally lay eggs, and meanwhile, the quality of the eggs and the semen is improved; by manually regulating and controlling the incubation of the fertilized eggs and the culture